2022
DOI: 10.1186/s12883-022-02873-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the epidemiologic, clinical, radiologic, and treatment methods of patients with subacute and chronic meningitis

Abstract: Background Meningitis is known as a meningeal inflammation accompanied by pleocytosis in the cerebrospinal fluid (CSF), and can be classified into acute, subacute, and chronic meningitis based on symptoms duration of ≤ 5 days, ≥ 5 days and ≥ 4 weeks, respectively. Subacute and chronic meningitis are caused mainly by indolent infectious agents and noninfectious causes such as autoimmune, and neoplastic. In this study, we investigated the characteristics, diagnosis, and treatment of subacute and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Moreover, testosterone can increase capsule production and decrease macrophage efficiency [ 25 ]. CM presents with insidious, progressive, subacute-to-chronic meningitis, a pattern that is also noted in the current investigation [ 11 ]. All the patients had mild symptoms, such as headaches, which were either ignored or not properly managed as neurological symptoms.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Moreover, testosterone can increase capsule production and decrease macrophage efficiency [ 25 ]. CM presents with insidious, progressive, subacute-to-chronic meningitis, a pattern that is also noted in the current investigation [ 11 ]. All the patients had mild symptoms, such as headaches, which were either ignored or not properly managed as neurological symptoms.…”
Section: Discussionsupporting
confidence: 72%
“…We performed a cross-sectional multicenter study across 15 Iranian hospitals in Alborz, East Azerbaijan, Fars, Gilan, Gorgan, Isfahan, Khuzestan, Lorestan, Mazandaran, and Tehran provinces from March 2021 to November 2022. Suspected patients were presented with either chronic (defined as presenting symptoms for a duration of at least 4 weeks) or subacute (defined as presenting symptoms for a duration of at least 5 days) meningitis symptoms, including fever, headache, meningismus, and altered mental status [ 10 , 11 ]. The CM cases were diagnosed by screening clinical manifestations, laboratory tests, and the hospital medical record information systems.…”
Section: Methodsmentioning
confidence: 99%
“…Our results presented 30.8% and 5.0% specificity with MRI and CT, respectively, on identifying meningitis-related findings in imaging. Previous study indicated MRI being more specific but with a lower specificity of 16% [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in one retrospective study of 79 patients with chronic meningitis, only 44.3% received a definitive diagnosis, 31.6% were bacterial (mostly Mycobacterium tuberculosis and Brucella spp.) and 10.1% were neoplastic (Bineshfar et al, 2022). Even with invasive diagnostic methods, i.e.…”
Section: Introductionmentioning
confidence: 97%